Chapter Il parco archeologico di Saturo (Leporano-TA) millenni di storia, decenni di incuria - Fabrizio, Fabio (Proceedings e report, 2020)
Alongside the Ionian Coast, 12 Km SE from Taranto there is the ancient settlement of Satyrion, one of the most significant places in the Mediterranean. The site has been inhabited since Neolitic to high Middle Age. The only intervention with a value had place at the end of the XX century, when the archeological area between Porto Perone and Porto Saturo was submitted to restoration, valorization and fruition works. The area of the Parco Archeologico di Saturo has been usable just for few years, collapsing in a terrible abandonment situation. Just in 2006 the area began to develop new interest.